Formulasi Gel Minyak Kulit Kayu Manis (Cinnamomum burmannii Bl) sebagai Sediaan Antinyamuk - Lukman, Anita; Susanti, Emma; Oktaviana, Roli (Jurnal Penelitian Farmasi Indonesia, 2013)
A study on gel formulation of cinnamomum oil as mosquito repellent has been done against Aedes aegypti. This study was aimed to determinethe most effective formula as mosquito repellent from two different concentrations of oil in gel formulation. Two different concentrations12 and 15% of cinnanmomum oil were formulated in to gel form with addition 1% of clove oil as its fixative. The formulation of bothconcentrations of cinnamomum oil resulted good gel formula based on its organoleptic, pH, homogeneity and physically stable. However,both formulas could cause skin irritation. Gel formula with 15% concentration of oil showed the most effective effect against Aedes aegyptiwith six hours of tested period.